LIPOMATOUS BULL DOG CALF MONSTER IN A MURRAH BUFFALO - SINGH, GYAN; PANDEY, A K; KUMAR, SANDEEP; SUNDER, SHYAM; KUMAR, RAKESH; DUTT, RAVI (The Indian Journal of Animal Reproduction, 2023)
A monster calf of lipomatous bull dog condition causing dystocia due to absolute feta-maternal disproportion in a Murrah buffalo is reported.